Penguatan Etika Kristiani tentang Keadilan dan Tanggung Jawab melalui Pendekatan Restorative Justice Konflik Lahan: Studi Kasus Penanganan di Kalimantan Tengah - Marlelo Marlelo (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study aims to analyze the role of strengthening Christian ethics regarding justice and responsibility as a moral compass in supporting the quality of restorative justice of land conflicts by the Central Kalimantan Regional Police. Using a qualitative approach of case studies. The results of the study found that Christian ethics had a significant positive influence on the success of recovery. The value of relational justice (theological tzedakah) motivates the victim to demand the restoration of dignity, while the concept of stewardship encourages the perpetrator (the corporation) to voluntarily admit wrongdoing and make a substantive commitment. Christian ethics serves as a moral catalyst that overcomes emotional resistance and power imbalance during mediation, triggers a narrative of forgiveness, and results in a more sustainable commitment to peace. Although restorative justice by the Central Kalimantan Police is procedurally effective, the model is still secular-procedural.